The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.25157/jall.v4i2.3682
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Strategies in Teaching Reading Comprehension

Abstract: This research aimed to figure out the strategies used by the English teachers in teaching reading and how they applied the strategies. This research was designed as descriptive qualitative research. The research was conducted at Junior High School 09 Bengkulu City. Participants of the research were two English teachers who teach in second grade of that school. Each English teacher had eigh meetings that observed by the researcher. The instruments of the research were strategies checklist and interview. The ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…There are kinds of teaching strategies used by EFL teachers in teaching reading skills. According to Dwiningtyas et al (2020), the strategies for teaching reading could be brainstorming, reading aloud, and asking for specific information. In addition, they mentioned the use of dictionaries, reading aloud, rereading to check comprehension, evaluating comprehension in particular tasks, and asking questions for specific information.…”
Section: A Introductionmentioning
confidence: 99%
“…There are kinds of teaching strategies used by EFL teachers in teaching reading skills. According to Dwiningtyas et al (2020), the strategies for teaching reading could be brainstorming, reading aloud, and asking for specific information. In addition, they mentioned the use of dictionaries, reading aloud, rereading to check comprehension, evaluating comprehension in particular tasks, and asking questions for specific information.…”
Section: A Introductionmentioning
confidence: 99%
“…The authors suggest that the teacher's experience of the Web-Quest tool, and the challenges to its integration in the blended learning classroom, should be investigated further. Dwiningtiyas et al (2020) also conducted a study entitled Teachers' Strategy in Teaching Reading Comprehension. They found that teachers used several strategies in teaching reading comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…According to the importance and problems mentioned above, the researcher found that reading comprehension in primary school, students should be trained in reading comprehension skills urgently so that they will know how to think critically, understand the stories they read correctly, and can capture the meaning of the story in a quick time. In addition, practicing reading comprehension skills is another method of teaching reading that can be used to solve problems in teaching reading comprehension (Nurdianingsih, 2021;Dwiningtiyas et al, 2020;Hans & Hans, 2015). Therefore, the researcher is interested in creating a skill exercise for practicing reading comprehension by experimenting with students to be a teaching instrument that will be able to respond to students to have better reading comprehension skills.…”
Section: Introductionmentioning
confidence: 99%